Відповідь:
3х-9=18
3х=27
х=27/3
х=9
пояснення:
3*9-9=18
x=27, y= 9.
Пошаговое объяснение:
Пусть первое число x, а второе y. Тогда, согласно условию, можно записать
Подставляя первое уравнение во второе, находим
Далее, получаем
Проверка:
Відповідь:
3х-9=18
3х=27
х=27/3
х=9
пояснення:
3*9-9=18
x=27, y= 9.
Пошаговое объяснение:
Пусть первое число x, а второе y. Тогда, согласно условию, можно записать
Подставляя первое уравнение во второе, находим
Далее, получаем![x=3*9=27.](/tpl/images/1220/2466/e6dc1.png)
Проверка: